2020
DOI: 10.1039/d0an00607f
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal distribution and speciation of silver nanoparticles in the healing wound

Abstract: First observation of AgNPs dynamics in the wounds of real patients through elemental imaging and speciation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…48 Roman et al detected the majority of silver nanoparticles in chronic wounds up to a depth of 1.5 mm. 20 We observed the association of silver with elastic and collagen fibers and localization around capillaries in the chronic wounds. Fredriksson et al observed a similar silver distribution pattern in ex vivo explanted human skin treated with the same silver dressing (Aquacel) as used in this study.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…48 Roman et al detected the majority of silver nanoparticles in chronic wounds up to a depth of 1.5 mm. 20 We observed the association of silver with elastic and collagen fibers and localization around capillaries in the chronic wounds. Fredriksson et al observed a similar silver distribution pattern in ex vivo explanted human skin treated with the same silver dressing (Aquacel) as used in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Enhanced levels of serum albumin in patients with chronic wounds serve for protection against increased silver concentrations in the blood 52 . The speciation of silver presented in a study by Roman et al suggested that silver binds predominantly to chloride in the upper layers (up 45 µm) and to glutathione in the deeper parts of the wound 20 . Therefore, silver‐protein complexes may well provide a silver removal pathway from wounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations